An outlook on coronavirus disease 2019 detection methods - Zahra Hassani Nejad; Fataneh Fatemi; Seyed Ehsan Ranaei Siadat (Elsevier, 2022)
Diagnostic testing plays a fundamental role in the mitigation and containment of coronavirus disease 2019 (COVID-19), as it enables immediate quarantine of those who are infected and contagious and is essential for the epidemiological characterization of the virus and estimating the number of infected cases worldwide. Confirmation of viral infections, such as COVID-19, can be achieved through two general approaches: nucleic acid amplification tests (NAATs) or molecular tests, and serological or antibody-based tests. The genetic material of the pathogen is detected in NAAT, and in serological tests, host antibodies produced in response to the pathogen are identified. Other methods of diagnosing COVID-19 include radiological imaging of the lungs and in vitro detection of viral antigens. This review covers different approaches available to diagnosing COVID-19 by outlining their advantages and shortcomings, as well as appropriate indications for more accurate testing.